Desenvolvimento de tecnologias para revegetação de sítios de extração de argila em tabuleiros costeiros - Costa, Kerwin Araujo (2021)
Clay exploration has been fundamental for the country's economic development, however, this activity is directly related to soil damage, due to the removal of its surface layers. The aim of this study was to evaluate the use of different techniques of revegetation and soil preparation, combined with ways of introducing arboreal species in the recovery of two sites degraded by clay exploration. The experimental areas were composed of a slope and a pit bottom of a deposit, in which the experimental design used was in randomized block in a 3x3 factorial scheme with 3 replications. For the slope, the compounds were composed by a combination of revegetation techniques (biomanta, hydroseeding and jute bag) and forms of introduction of arboreal vegetation(Only arboreal species, arboreal species simultaneously to the mix of herbaceous and arboreal species six months ago after the mix) and for the bottom of the pit were composed by the combination of soil preparations(scarification, scarification + harrowing and subsoiling + harrowing) and forms of introduction of arboreal vegetation, as occurred on the slope. For the two experiments, soil density, total porosity, macroporosity and microporosity, soil resistance to penetration, aggregate stability, permeability and soil fertility were determined. Both on the slope and at the bottom of the pit, the treatments promoted increases in the physical and chemical attributes of the soil, although many of them did not differ from the evaluation carried out before the implementation of the experiment. There was a remarkable improvement in the total porosity of the soil and distribution of macro and micropores, close to the ideal condition. The lower values of penetration resistance and the increase in the values of chemical attributes for the 0-5 cm layer allowed the development of introduced plant species for revegetation of the clay deposit, even with edaphic limitations observed at 24 months.